Communications and multimedia security 10th IFIP TC-6 TC 11 international conference, CMS 2006, Heraklion Crete, Greece, October 19-21, 2006: proceedings - IFIP TC6/TC11 International Conference on Communications and Multimedia Security (Lecture notes in computer science, 2006)
This book constitutes the refereed proceedings of the 10th IFIP TC-6 TC-11 International Conference on Communications and Multimedia Security, CMS 2006, held in Heraklion, Crete, Greece in October 2006. The 22 revised full papers presented were carefully reviewed and selected from 76 submissions. The papers are organized in topical sections on applied network and information security, identification and authentication, DRM and multimedia security, Web and XML security, cryptography, privacy and data protection, as well as network and information security analysis and modeling. Computing of trust in ad-hoc networks -- TAO: protecting against hitlist worms using transparent address obfuscation -- On the privacy risks of publishing anonymized IP network traces -- Secure mobile notifications of civilians in case of a disaster -- A fair anonymous submission and review system -- Attribute delegation based on ontologies and context information -- Adding support to XACML for dynamic delegation of authority in multiple domains -- One-round protocol for two-party verifier-based password-authenticated key exchange -- Enhanced CAPTCHAs: using animation to tell humans and computers apart -- Perturbing and protecting a traceable block cipher -- A new encryption and hashing scheme for the security architecture for microprocessors -- Timed release cryptography from bilinear pairings using hash chains -- Compression of encrypted visual data -- Selective encryption for hierarchical MPEG -- Equivalence analysis among DIH, SPA, and RS steganalysis methods -- A flexible and open DRM framework -- PPINA – A forensic investigation protocol for privacy enhancing technologies -- A privacy agent in context-aware ubiquitous computing environments -- Ensuring privacy in smartcard-based payment systems: a case study of public metro transit systems -- Attack graph based evaluation of network security -- Information modeling for automated risk analysis -- Towards practical attacker classification for risk analysis in anonymous communication.